Sustainability of African Cultural Epistemology through Cultural Re-Appropriation in Selected Works of Emerging African Scholars - Mpako, Nombeko Penelope (Cultural Arts Research and Development, 2026)
This article explores indigenous cultural epistemology rooted in African culture and tradition through cultural re-appropriation presented in selected research projects by emerging African scholars. It seeks to contribute to the sustainable development of African knowledge systems and how they can be integrated into contemporary practice. This involves unpacking the unique perspectives, norms, values, and practices embedded in African cultures and how they relate to social justice and community well-being. Set within decolonial theories, it critically engages with postgraduate research conducted in collaboration with an academic supervisor to elucidate how Indigenous knowledge systems are being revitalized and positioned within contemporary scholarly discourses. It analyses and interprets a selection of collaborative projects to underscore the epistemic value of African cultural paradigms and the transformative potential of cultural re-appropriation in resisting colonial knowledge hierarchies. The findings highlight how the mutual metacognitive teaching and learning methodology applied in this research actively contributes to the sustainability of Indigenous cultural knowledge, offering a dynamic foundation for future academic inquiry where teaching and learning are reciprocal processes. Ultimately, the article asserts that the teaching and learning method applied in this research, as well as the constructive re-appropriation of African cultural epistemology, not only affirms identity and heritage but also challenges dominant global narratives, reinforcing the relevance of Indigenous thought within international academic contexts.